DIE BELEG EN ONTSETTING VAN LADYSMITH - Van Tonder, A.G.W. (Scientia Militaria - South African Journal of Military Studies, 2012)
Beginning with the initial confrontation between a republican commando of about 1 000 men under General Cronje and British forces under General French in October, 1899, the writer traces the course of events through the Boer siege of Ladysmith and the initially ineffectual manoeuvres of General Buller until the latter’s forces eventually liberated Ladysmith in march 1900. He also points to certain tactical mistakes committed by the Boer leaders is not following up their victory at Modderspruit and in taking the decision to besiege Ladysmith whereby they tied up large numbers of Boer troops who might have been used elsewhere with far greater effect.